The Impact of Quality indicators on Quality of Primary Education in Khyber Pakhtunkhwa - Shah, Sayyed Farooq; Ghazi, Safdar Rehman; Shahzad, Saqib; Ullah, Irfan (American Journal of Humanities and Social Sciences, 2015)
Education plays a major role in the development of a state. It is extensively accredited that quality of primary education is the solo most important tool in strengthening human capabilities and achieving the desired goals. The major purpose of the study was to know how the quality indicators impact the quality education in government boys and girls primary schools of the selected five southern districts of Khyber Pakhtunkhwa, Pakistan. All the head teachers and teachers of government primary schools of southern districts of Khyber Pakhtunkhwa constituted the population of the study. The sample of the study was consisted of 100 head teachers (50 male and 50 female) and 300 teachers (one hundred & fifty male and one hundred & fifty female). The study was a survey type in nature. To collect the relevant information on the selected quality indicators (quality of learning environment, quality of contents, quality of process, and quality of outcomes) a self-developed questionnaire was used. Statistical tools chi square test of goodness of equal probability and chi square test of independence were used to analyze the data. In the light of conclusions it is recommended that separate staffrooms should be constructed for teachers, sufficient books for learners and supplementary/allied reading materials for teachers should be provided well in time, students should be encouraged to ask relevant questions during the teaching. Furthermore, examination and assessment systems should be impartial and transparent. Therefore examinations conducting bodies/ authorities should be appointed on merit basis, papers or assessment work may be done by expert teachers, supervisory staff may necessarily be nominated on best performance basis, and evaluation process might to be administered by skilled personals.